Home Energy Management System and Internet of Things: Current Trends and Way Forward - Wan Ahmad, Wan Siti Halimatul Munirah; Mohamed Radzi, Nurul Asyikin; Balasubramaniam, Nagaletchumi (International Journal of Integrated Engineering, 2021)
Managing energy in the residential areas has becoming essential with the aim of cost saving, to realize a practical approach of home energy management system (HEMS) in the area of heterogeneous Internet-of-Thing (IoT) devices. The devices are currently developed in different standards and protocols. Integration of these devices in the same HEMS is an issue, and many systems were proposed to integrate them efficiently. However, implementing new systems will incur high capital cost. This work aims to conduct a review on recent HEMS studies towards achieving the same objectives: energy efficiency, energy saving, reduce energy cost, reduce peak to average ratio, and maximizing user's comfort. Potential research directions and discussion on current issues and challenges in HEMS implementation are also provided.